PELAKSANAAN KOMUNIKASI PEMBANGUNAN PROGRAM JAMINAN KESEHATAN NASIONAL BPJS KESEHATAN DI KOTA PEKANBARU - ", Fredelina; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The national health guarantee program that under shade of BPJS kesehatan which has the kinds of healty service these are new program which made by Kementrian Kesehatan RI. Health service of BPJS will be held on Januari 1 st 2014, which has main purpose: to fulfill health society’s need that will given to every people who has paid the contribution or paid by goverment. By this program , every people will get health service.The theory used in this research is the process of communication or socialization according to Harold Laswell, who explained that in process of communication or socialization is answer the questions, who, says what, in which channel, to whom, with what effect. This research uses qulitative research methods, and the data collecting is obtained from the documentation and circumstantial to informan.After finishing this research, the implementation of development communication JKN by BPJS Kesehatan with the kinds of activities that supporting the implementation of communication still out of maximum, it’s because realization of sosialiszation is not spread over to all people even BPJS Kesehatan kota Pekanbaru already giving kinds of health program service. It also founded factors which influence the implementation development program JKN BPJS Kesehatan in Pekanbaru. Those factor are technical disturbance, semantic disturbance, limitation of human resourches in implementing sosialiszation, the limitation of tools and infrastructure support. The suggestion of implementation development communication of JKN BPJS Kesehatan program, and then it must more upgrade the socialiszation have to give periodicly to the society and service has to more completely and tools and infrastructure health which support this program.Keywords : National Health Of Guarantee, Implementation Program, Health Services